Problems of Economic Security for Digital Society in the Context of Globalization - Popov, Evgeny Vasilyevich; Semyachkov, Konstantin Aleksandrovich (Economy of Regions, 2018)
The purpose of the study is to systematize the challenges of the public economic security in the context of the development of global digitalization. The paper shows that the priority task of economic security, particularly notable in the rapidly changing conditions of today’s globalized world, is to predict the challenges and threats of general digitalization. We have highlighted the features of the digital economy development, which include the intellectual assets, the increase of the relevance of data, network management, wide Internet penetration as well as global data exchange. In the conditions of the digital economy, we have grouped the issues of economic security on system, structural and sectoral problems, as well as the problems of enterprises and individuals. The main problems of economic security are the issues of «digital inequality», a lack of own element base, changes in the labour market, industrial intelligence, personal data manipulation, etc. We have found tools for solving the issues of digital society. These tools include digital platforms for the development of «shared economy», as well as cloud technologies and methods for processing large databases. The Network Readiness Index is a tool for monitoring the development of network digital society. We have formulated the principles for constructing systems for the development of skills, which allow solving the problems of the public economic security in the conditions of digitalization. These principles include the rational use of resources combining short-term and long-term development goals, lifelong learning, consistency, unified approach to management at different levels as well as involvement stakeholders in the process of digitalization. The results of this paper can be useful to public authorities for the development of the principles of digital economy management, as well as to the representatives of scientific community for the study of the economic security issues in the conditions of digital society development.